Role of blockchain games in shaping the cryptoculture of digital ecosystems - Smolikova, Tatiana M. (Human in the Socio-Cultural Dimension, 2025)
The article explores the role of blockchain games in the formation and development of cryptoculture within modern ecosystems. The game model play-to-earn as a key element contributing to the implementation of blockchain technologies into the daily life of users is considered. The mechanisms of staking and the use of non-fungible tokens in gaming ecosystems are analysed. Special attention is paid to the impact of blockchain games on the formation of new economic models and social interactions in virtual space. The article touches upon the adaptation of global blockchain gaming trends in the Russian-speaking segment of digital ecosystems. Discusses potential prospects and challenges related to the further development of blockchain games and their role in the evolution of cryptoculture.